Numerical simulations of flow interactions between steep hill terrain and large scale wind turbine. (15th May 2018) - Yan, Shu; Shi, Shaoping; Chen, Xinming; Wang, Xiaodong; Mao, Linzhi; Liu, Xiaojie
Abstract: With the scale of wind turbine increasing, the obstructing effect of wind turbine to the surrounding flow of local terrain is getting more remarkable. This influence is seldom considered in current micro-siting of complex-terrain wind farms. The present paper investigates the flow around hills with different Height/Width (H/W) ratios, as well as the interactions between the surrounding flow using three dimensional numerical simulations. A 2 MW wind turbine is placed on five different locations. The simulation results show that the power production could be over-predicted by more than 10% if the wind turbine is not modeled in the computational processes. The H/W ratio which has significant influence on the flow structure around the hill. For the hill with a small H/W ratio, the surrounding flow has little variation with and without wind turbine. For the hill with a large H/W ratio, large scale flow separation occurs on the lee side under the wind turbine disturbances. The flow separation on the lee side also occurs when the wind turbine is located upwind in certain distance to the hill. The results indicate that the mutual interactions between wind turbine and terrain must be considered in the micro sitting of complex-terrain wind farms. Highlights: The obstructing effect of large-scale wind turbine to the flow over complex terrain is investigated. The variations of the surrounding flow of hill with and without wind turbine disturbing are illustrated and analyzed. The effect of an influential factor, aspect ratio of the hill, to the flow variations is revealed.